Compliance of Time Sensitive Network Protocol with the Specifications of MIL-STD-1553B Standard for Aviation Applications - Fakhroddin Nazari; Rasoul Hajizadeh; Mohammad Abbasi (مجله مدل سازی در مهندسی)
In this article, the time-sensitive networking protocol on the MIL-STD-1553 data bus is implemented and evaluated to reduce the average packet reception delay. The most important feature of this bus is its high reliability. One of the parameters addressed in this bus is the certainty of data arrival along with the defined delay, meaning the bus is designed in a way that the probability of creating delays beyond the standard does not exist. However, despite all the good properties of this bus, its low speed is not suitable for modern systems today. In this article, the delay issue and its guarantee based on time-sensitive networking are examined. The proposed method prioritizes packets exchanged in the 1553 data bus. OMNET++ software is used for implementation, and simulation results show that delays have been less compared to the 1553 bus, and while the size of these delays remains constant, their amount is almost constant under conditions where there is an increase in data volume and its transfer rate. The proposed time-sensitive protocol reduces the average maximum network delay by 86 percent.